Exploring the antibacterial activity of endophytic bacteria from Andaliman (Zanthoxylum acanthopodium DC.) against Bacillus subtilis - DEBIE RIZQOH; SIPRIYADI SIPRIYADI; UTARI HARTATI SURYANI; CINTYA NABILA PUTRI; MEUTIA AGUSTIN; HERNITA TAURUSTYA; NOVRIANTIKA LESTARI; MARDHATILLAH SARIYANTI (Biodiversitas Journal of Biological Diversity, 2024)
Abstract. Rizqoh D, Sipriyadi, Suryani UH, Putri CN, Agustin M, Taurustya H, Lestari N, Sariyanti M. 2024. Exploring the antibacterial activity of endophytic bacteria from Andaliman (Zanthoxylum acanthopodium DC.) against Bacillus subtilis. Biodiversitas 25: 700-707. Infectious diseases are still one of the global health problems. Increasing antibiotic resistance against several pathogenic microbes causes antibiotics to be less effective in treating infectious diseases. One pathogenic bacteria that causes infection is Bacillus subtilis, which causes bacteremia, septicemia, and endocarditis. Therefore, searching for new alternative antibiotics is urgently needed to overcome bacterial resistance. Andaliman (Zanthoxylum acanthopodium DC.) extract produces antimicrobial bioactive compounds. Thus, this study aims to explore endophytic bacteria from Z. acanthopodium and determine their antibacterial activity against Bacillus subtilis. This study used a qualitative experimental method, namely isolation of endophytic bacteria, characterization of endophytic bacteria colonies and cells, antagonistic test against B. subtilis, extraction of compounds from endophytic bacteria, and determine Minimum Inhibitory Concentration (MIC) of crude extract of endophytic bacteria against B. subtilis. This study showed that 16 endophytic isolates from Z. acanthopodium could inhibit the growth of B. subtilis, and potential isolates were EA7 and EA26, which have Minimum Inhibitory Concentration (MIC) at 40%, and EB6 at 80%.